Case report: Efficacy of immune checkpoint inhibitors for high tumour mutational burden malignant phyllodes tumours of the breast as revealed by comprehensive genomic profiling - Katsuya, Hiroo; Sano, Haruhiko; Sano, Haruna; Mihashi, Tatsuya; Nakashima, Chiho; Kai, Keita; Kimura, Shinya (Frontiers in Immunology, 2025)
High tumour mutational burden (TMB-high), identified through comprehensive genomic profiling (CGP), is a biomarker that predicts the efficacy of immune checkpoint inhibitors. CGP testing is recommended for rare cancers with limited effective treatment options. Here, we provide the first report of a malignant phyllodes tumour of the breast demonstrating TMB-high status and effective treatment with pembrolizumab. The patient initially underwent right breast tumour resection and was diagnosed with a malignant phyllodes tumour. Recurrence was observed at the same site with metastases to the pulmonary hilar and right axillary lymph nodes. CGP testing revealed TMB-high status and microsatellite stable. Pembrolizumab was initiated after chemotherapy for the soft tissue sarcoma. After two treatment cycles, imaging revealed a partial response of the pulmonary hilar lymph nodes and necrotic enlargement of the right axillary lymph node. After four cycles, all lymph nodes had reduced in size. Eight months after ten cycles of pembrolizumab treatment, multiple new nodules were observed in both lungs, indicating disease progression. This case highlights the utility of CGP testing in rare cancers, demonstrating the first evidence of TMB-high malignant phyllodes tumours of the breast responding to pembrolizumab and underscoring the value of expanding CGP testing to improve therapeutic strategies for rare cancers.